Respons Siswa terhadap Penggunaan Aplikasi Wordwall pada Pembelajaran Teks Berita Kelas VII SMP Negeri 3 Pringgarata - Anantha , Andika Putri; Wirahyuni , Kadek; Indriani , Made Sri (Jurnal Penelitian Mahasiswa Indonesia, 2023)
Teachers as one of the main components must be able to understand students and manage their learning paths so that they can shape students' abilities and character. A teacher must also be capable of creating an interesting learning environment to stimulate students' learning motivation or interest. The use of interactive learning media can help optimize student learning interests, one of which is the Wordwall application. Therefore, the study focuses on student responses to the use of the Wordwall application in the learning of news text in the VIIA of SMP Negeri 3 Pringgarata. The subjects of this study are students of the VIIA of SMP Negeri 3 Pringgarata while the object of this research is the student's response to learning news text using the wordwall application. Data collection methods include observations, tests, documentation, and questionnaires. The data analysis techniques used are qualitative descriptive. The findings in this study were the average response data of students to the use of Wordwall applications obtained from Cycle I action was 41.7% which was in the positive category, while the average student response data to the application Wordwall received from the Cycle II action was 46.5% which was in the very positive category.